2016
DOI: 10.1039/c6ra02174c
|View full text |Cite
|
Sign up to set email alerts
|

Ru doping enhanced resistive switching behavior in InGaZnO thin films

Abstract: In this paper, ruthenium (Ru) doped InGaZnO (IGZO:Ru) thin films were deposited by magnetron co-sputtering and the resistive switching behaviors were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[1][2][3][4] Alternately, electrical resistance switch-based memory (RRAM) has attracted intense research interest as a promising candidate for use in next-generation non-volatile memory due to its high scalability down to a few nanometers and high-density integration with CMOS technology. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Conventional devices consist of a metal-insulator-metal (MIM) structure, with insulator resistance switching caused by the diffusion of oxygen vacancies/defects, charge carrier trapping and de-trapping, and Schottky barrier modulation to produce the memory effect. 5 Even though many dielectric materials such as HfO x (ref.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Alternately, electrical resistance switch-based memory (RRAM) has attracted intense research interest as a promising candidate for use in next-generation non-volatile memory due to its high scalability down to a few nanometers and high-density integration with CMOS technology. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Conventional devices consist of a metal-insulator-metal (MIM) structure, with insulator resistance switching caused by the diffusion of oxygen vacancies/defects, charge carrier trapping and de-trapping, and Schottky barrier modulation to produce the memory effect. 5 Even though many dielectric materials such as HfO x (ref.…”
Section: Introductionmentioning
confidence: 99%
“…From the endurance characteristics shown in Figure 4f, a high on/off ratio of ≈10 4 was identified, which is 2–3 orders higher than those available in the literature of IGZO memristors with Ag TE [ 26,27 ] and comparable to the highest ratio of 10 5 previously achieved in IGZO‐based memristors doped with Ru. [ 25 ] This huge on/off ratio indicates that the switching mechanism is clearly governed by ECM in the IGZO memristors with Ag TE, rather than VCM, as is reported that the EMC leads to a much higher memristor on/off ratio due to the dominating contribution of metal ions than those governed by the VCM. [ 60 ] Therefore, the Ag ions oxidized from the TE are attributed to the governing switching characteristic of the device.…”
Section: Resultsmentioning
confidence: 83%
“…Although various combinations of electrode materials for memristor applications are available in the literature, the behavior of reported memristors, despite the same switching and electrode materials, is considerably inconsistent in their performance. [25][26][27] Enhanced understanding of the RS mechanism and the effect of metallization on the performance may address the conflicted behaviors and further advance the memristor technology.…”
Section: Introductionmentioning
confidence: 99%
“…During the reset process, the oxygen ions can be released from the top electrode under the negative bias voltage. These ions may move back to the IGZO film and neutralise oxygen vacancies, leading to a breakage of the filaments and hence the HRS [35]. The ReRAMs with the oxygen plasma treatment were also examined with different active areas to verify the filament model.…”
Section: Resultsmentioning
confidence: 99%
“…Pei et al showed that inserting a SiO2 buffer layer into IGZO ReRAM devices can improve the resistive switching ratios [33]. Various treatments of IGZO layers have also been made to improve the performance of ReRAMs, e.g., using ultraviolet (UV) irradiation [26], microwave irradiation [34] and element doping [35]. Moreover, the effects of electrode materials on device characteristics have been studied [36], [37].…”
Section: Introductionmentioning
confidence: 99%